1999
DOI: 10.1007/s001340051050
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prone position on alveolar recruitment and oxygenation in acute lung injury

Abstract: Alveolar recruitment may be a mechanism of oxygenation improvement in some patients with acute hypoxemic respiratory failure. No correlation was found between change in oxygenation and chest wall elastic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(56 citation statements)
references
References 25 publications
(30 reference statements)
3
52
0
1
Order By: Relevance
“…Prone positioning, reported for the first time in 1976 by Piehl et al [79] has a special place in lung recruitment. Most studies found an improvement in oxygenation, although a substantial number of patients do not respond and the beneficial effect usually disappears after reversal to the supine position [60,70,71,[80][81][82][83][83][84][85][86]. The increase in oxygenation in the prone position is explained by recruitment-related mechanisms such as improved ventilation through decreased alveolar compression by the heart and recruitment-independent mechanisms, e.g.…”
Section: Human Studiesmentioning
confidence: 99%
“…Prone positioning, reported for the first time in 1976 by Piehl et al [79] has a special place in lung recruitment. Most studies found an improvement in oxygenation, although a substantial number of patients do not respond and the beneficial effect usually disappears after reversal to the supine position [60,70,71,[80][81][82][83][83][84][85][86]. The increase in oxygenation in the prone position is explained by recruitment-related mechanisms such as improved ventilation through decreased alveolar compression by the heart and recruitment-independent mechanisms, e.g.…”
Section: Human Studiesmentioning
confidence: 99%
“…26) The following mechanisms underlying the respiratory effects observed in the prone position have been suggested: improved redistribution of ventilation in the dorsal lung areas, an increased tidal volume in relation to modulated chest wall movement, 27) alveolar recruitment, 28) alterations in compressive forces exerted by the heart on the lungs 29) and improved clearance of secretions. 30) In contrast to that observed in the lateral decubitus position, in the prone position, the mediastinal structures lie naturally and the chest and abdomen are free of compression.…”
Section: Respiratory and Circulatory Physiology In The Prone Positionmentioning
confidence: 99%
“…35) Using the PP to improve the operative view, some surgeons have been able to operate without the use of onelung ventilation via a double-lumen endotracheal tube. 28) The absence of one-lung ventilation reduces arteriovenous shunting with superior preserved oxygenation. 24,36) Therefore, the use of two-lung ventilation, or at least partial lung deflation, in the PP may reduce the incidence of collapsed lung and the need for reinflation of the lungs which are well known to produce inflammatory mediators, 37) possibly resulting in a reduction in the frequency of pulmonary-related complications, although this hypothesis remains unproven clinically.…”
Section: Respiratory and Circulatory Physiology In The Prone Positionmentioning
confidence: 99%
“…The contraindications are hemodynamic compromise, high intracranial pressure (15), pregnancy, lung emphysema, bronchopleural fistula, pneumothorace and right heart failure. Several methods have been described to perform recruitment maneuver: sights (16), sustained inflation (17), staircase method (14), and prone positioning (18). The volume of lung recruited during a recruitment maneuver is a combination of pressure and time.…”
Section: Recruiting the Lungmentioning
confidence: 99%